Output and Staff Number in Hungarian Manufacturing before, during and after the Crisis - Bereczk, Ádám (Theory, Methodology, Practice – Review of Business and Management, 2013)
The paper describes outcomes of recent research about connection between output and staff number related to specific sectors of manufacturing in Hungary. The method was to examine the existence of a linear relationship between the variables with cross correlation and regression modelling. The examined period includes the nadir of the crisis and the first years of recovery. In the textile and food industries co-movement of time series show a strong correlation between output and staff number. There is a strong positive correlation in the case of the automotive industry, but no linear relationship can be proved between the variables in the chemical industry.